ANALISIS KESEPIAN SEBAGAI KRISIS RELASIONAL DALAM GEREJA DAN IMPLIKASI PASTORAL - Fandy Mulya Latif; Juliana Hindradjat (PT. Giat Konseling Nusantara, 2026)
This article examines loneliness as a multidimensional phenomenon through an integrative theological–psychological analysis within the context of contemporary Christian pastoral care. The purpose of thisstudy is to identify the core dynamics of loneliness, evaluate its theological implications based on therelational nature of the imago Dei, and formulate an integrative pastoral model that responds effectively tothe relational, cognitive, and communal needs of church members. The theoretical framework combinesrecent psychological findings on cognitive distortions and maladaptive relational patterns with Christiantheological perspectives on human relationality, ecclesiology, and the role of the Holy Spirit in restoringhuman relationships. This study employs a qualitative-descriptive method through a systematic literaturereview of research published between 2014 and 2025, complemented by analysis of theological sourcesand biblical texts. The findings reveal that loneliness is sustained by cognitive biases, relationalfragmentation, and structural limitations within church communities, while theology provides anontological basis for restoring disrupted relationships. This study concludes that an integrative pastoralmodel that incorporates cognitive reframing, relational restoration, and spiritual formation is necessary toaddress loneliness comprehensively within the life of the church.